2019
DOI: 10.3390/pr7090564
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effects of Injection Fluctuations on Liquid Nitrogen Spray Cooling

Abstract: Spray cooling with liquid nitrogen is increasingly utilized as an efficient approach to achieve cryogenic cooling. Effects of injection mass flow rate fluctuations on the evaporation, temperature distribution, and droplet distribution of a spray field were examined by employing a validated Computational Fluid Dynamics (CFD) numerical model. The numerical results indicated that injection fluctuations enhanced the volume-averaging turbulent kinetic energy and promoted the evaporation of the whole spray field. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It is reported that the flow and diffusion characteristics will be greatly affected in a complex unsteady flow field yielded by the different release pressures [20]. Different from the conventional…”
Section: Degree Of Superheat Under Different Release Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the flow and diffusion characteristics will be greatly affected in a complex unsteady flow field yielded by the different release pressures [20]. Different from the conventional…”
Section: Degree Of Superheat Under Different Release Pressuresmentioning
confidence: 99%
“…It is reported that the flow and diffusion characteristics will be greatly affected in a complex unsteady flow field yielded by the different release pressures [20]. Different from the conventional liquid jet, which is greatly dependent on the surface evaporation of the broken liquid droplets, the thermodynamic parameters are the main factors that affect the jet characteristics of the gas fire extinguishing agent.…”
Section: Degree Of Superheat Under Different Release Pressuresmentioning
confidence: 99%
“…Due to the particularity of the aircraft as an important air traffic tool, extremely high requirements for both reliability and economy are put forward for the performance of its fire extinguishing system [2][3][4][5]. As an important component of fire extinguishing systems, nozzles usually have a vital impact on the flow and release characteristics of the extinguishing agent, and their release performance has become one of the hot spots of the fire extinguishing technology research in recent years [6][7][8][9][10][11][12][13][14]. Studies have shown that even if the nozzle structure is axisymmetric, the flow field inside it will be asymmetrically distributed [14].…”
Section: Introductionmentioning
confidence: 99%
“…The application was used as an open cycle in a cooling system. Moreover, Xue et al [15] showed in their study, the influence of different injection pressures on the nozzle inside diameter, the mass flow rate, drop size distribution, discharge coefficient, spray flow pattern, and spray cone angle were studied. Most recently, Wang et al [16] were conducted theoretical analysis and numerical study liquid nitrogen spray as a cryogenic cooling fluid in electronic equipment under low pressure.…”
Section: Introductionmentioning
confidence: 99%